Старуха Изергиль: [рассказы, пьеса] / Максим Горький - Горький Максим (Классика в школе, 2014)
Экземпляры: ф. 15 (20150908) / Инвентарный номер: 50711 / Цена: 115.00 / Авт.знак: Г 71 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6